An EUCS-Based Analysis of Student Satisfaction with ShopeePay - Egi E. Ningsih; Beni Irawan; Dwi A. Gusriyanti; Amroni (Media Journal of General Computer Science, 2026)
ShopeePay is one of the digital wallet services widely used in online and offline transactions, especially among students. As part of the Shopee ecosystem, ShopeePay is expected to provide convenient, accurate, and satisfying services for its users. However, several limitations, such as the absence of cash withdrawal features, virtual debit cards, and investment services, may affect user satisfaction. These issues indicate the need for an evaluation of ShopeePay from the perspective of end users. This study aims to analyze the factors that influence user satisfaction with the ShopeePay application using the End User Computing Satisfaction (EUCS) model. The research adopts a quantitative approach by distributing questionnaires to students of Universitas Dinamika Bangsa (UNAMA) who actively use ShopeePay. The EUCS variables examined include Content, Accuracy, Format, Ease of Use, and Timeliness. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software and bootstrapping techniques. The results show that three variables significantly affect user satisfaction, while two variables do not. Among all variables, Format has the strongest influence on user satisfaction, highlighting the importance of interface design and information presentation.